3D design and study on fatigue specimens for metal printing - Eng, Kang Jun (Nanyang Technological University, 2024)
Design study and work were carried out for the MAM baseplate. For IN718 and Ti-6Al-4V, manufactured with SLM 280 2.0. With power up to 400W, 0.03mm layer thickness and varied hatching distance and velocity, two baseplates of the same design were produced for testing, while more design was created and to be printed in the future. Fatigue tests were carried out with 50Hz frequency and 0.1 stress ratio on Shimadzu Servco Pulser Fatigue Testing Machine with 4830 Controller. Tensile and fatigue test results were ideal and outstanding for IN718, but due to poor printing of Ti-6Al-4V, manufacturing defects were observed on the surface before the test was conducted, hence did not perform as well. The purpose of the report was to verify the uniformity of mechanical properties of specimens printed across the baseplate and study any possible factor to improve the properties, in terms of allowance between each part printed. Ultimately, the report was able to present good results aligned with the intention of the studies.